Anisi Stellati Fructus, a Significant Traditional Chinese Medicine (TCM) Herb and Its Bioactivity against Gastric Cancer. (9th May 2022) - Khan, Maryam; Shamim, Saba
Abstract : Anisi stellati fructus (ASF) is the fruit of Illicium verum Hook F. (Chinese star anise), which is native to many countries, and is a significant Chinese medicinal herb. Gastric cancer (GC) is one of the major fatal types of cancers with multiple stages and a poor prognosis. The present review aims to discuss the bioactive properties of ASF and its phytocompounds against GC, with a particular insight into the molecular mechanisms and signaling pathways involved in its anti-GC mechanism. Furthermore, it highlights the potential mechanism of action of major phytocompounds of ASF against GC. Clinical studies ( in vitro and in vivo ) regarding the action of ASF and its major bioactive compounds such as quercetin, luteolin, kaempferol, d-limonene, and honokiol against GC were reviewed. For this review, search of literature was performed in Science, PubMed, Google Scholar, Web of Science, and Scopus related to ASF and its phytocompounds, from which only relevant studies were chosen. Major bioactive compounds of ASF and their extracts have proven to be effective against GC due to the mechanistic action of these compounds involving signaling pathways that target cancer cell apoptosis, proliferation, and tumor metastasis in GC cells. Existing reports of these compounds and their combinatory effects with other modern anticancer agents have also been reviewed. From its traditional use to its role as an anticancer agent, ASF and its bioactive phytocompounds have been observed to be effective in modern research, specifically against GC. However, further studies are required for the identification of molecular targets and pharmacokinetic potential and for the formulation of anti-GC drugs.